PELAKSANAAN PERJANJIAN HAK PAKAI TOKO / KIOS ANTARA PEDAGANG DAN DINAS PERDAGANGAN KOTA PADANG DI PASAR RAYA PADANG - Diko Fazrian; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The market is an important place for humans to carry out various economictransactions, the market is a place that provides clothing, food, and shelter needs to meetthe primary needs of humans.The existence of Pasar Raya Padang is managed by thegovernment, namely the Trade Office of the City of Padang. In the implementation of theagreement to use the store / kiosk at the Padang highway market loaded in the bookholder of the right to use the shop / kiosk owned by the trader, in the book there areseveral articles, precisely in Article 3 reads